Chemical and Structural Changes in Corn Stover After Ensiling: Influence on Bioconversion - Nagle, Nick J.; Donohoe, Bryon S.; Wolfrum, Edward J.; Kuhn, Erik M.; Haas, Thomas J.; Ray, Allison E.; Wendt, Lynn M.; Delwiche, Mark E.; Weiss, Noah D.; Radtke, Corey (Frontiers in Bioengineering and Biotechnology, 2020)
Production of biofuels, bioproducts and bioenergy requires a well-characterized, stable, reasonably uniform biomass supply and well-established supply chains for shipping biomass from farm fields to biorefineries, while achieving year-round production targets. Preserving and stabilizing biomass feedstock during storage is a necessity for cost-effective and sustainable biofuel production. Ensiling is a common storage method used to preserve and even improve forage quality; however, the impact of ensiling on biomass physical and chemical properties that influence bioconversion process has been variable. Our objective in this work was to determine the effects of ensiling on lignocellulosic feedstock physicochemical properties and how that influences bioconversion requirements. We observed statistically significant decreases (p<0.05) in the content of two major structural carbohydrates (glucan and xylan) of 5% and 8%, respectively, between the ensiled and non-ensiled materials. Pretreatment and enzymatic hydrolysis of the ensiled materials produced similar sugar yields from structural carbohydrates (p<0.05) compared to non-ensiled controls. Based on this work, ensiling the corn stover did not change the bioconversion requirements compared to the control samples and incurred losses of structural carbohydrates. At the light microscopy level, ensiled corn stover exhibited little structural change or relocation of cell wall components as detected by immuno-cytochemistry. However, more subtle structural changes were revealed by electron microscopy as ensiled cell walls exhibit ultra-structural characteristics such as wall delimitation intermediate between non-ensiled and dilute acid pretreated cell walls. These findings suggest that alternative methods of conversion, such as deacetylation and mechanical refining (DMR), that could take advantage of lamellar defects and may be more effective than dilute acid or hot water pretreatment for biomass conversion of ensiled materials.